Writing for Academic Journals in the Digital Era. (April 2020) - Paltridge, Brian
The use of digital technologies has transformed the processes of writing for academic journals and the dissemination and preservation of academic work. It has also made the measurement of the impact of publications in academic journals easier and this information more accessible to authors. In this article I discuss some of the ways in which digital technologies have changed writing for academic journals as well as how digital technologies are being used in the submission and review of journal articles. This includes ways in which academic work can be stored and shared, the use of citation management tools, and the sharing of research materials once an article has been accepted for publication. I also give an overview of how digital technologies are being used in the review of journal articles including the use of plagiarism detection software. Issues in online publishing are outlined as is the development of open-access journals and the rise of predatory publishers. Social media and journal publishing and the use of multimodality in research article writing are also discussed.